Frictional performance of chemically modified cottonseed-based fossil-free biolubricant oil in a sliding tribopair - Ghumman, I. S. S.; Afaq, S. K.; Usman, Ali (Frontiers in Mechanical Engineering, 2023)
In this study, the tribological properties of a green lubricant synthesized from cottonseed oil through a two-step transesterification process are investigated, with a specific focus on the maximum throughput of the second step that involves the reaction of cottonseed methyl ester with 2-ethyl-1-hexanol alcohol and a titanium isopropoxide (TIS) catalyst. The research centers on evaluating the physiochemical characteristics of this bio-lubricant and comparing them with those of commercial oil (5W30) and the ISO VG40 standard. Furthermore, the influence of crucial process variables, such as temperature, pressure, reaction time, and TIS catalyst concentration, is examined by analyzing variance in experimental data. Fourier transform infrared (FTIR) analysis is employed to identify functional groups, particularly emphasizing the impact of temperature and reaction time. By optimizing the second transesterification process under specific conditions (pressure = 19.42 mmHg, temperature = 175°C, catalyst concentration = 0.63%, and reaction time = 4.0 hr), a cottonseed oil-based bio-lubricant is successfully produced, exhibiting properties comparable to those of commercial mineral lubricants. Notably, the findings reveal significant enhancements in the coefficient of friction (CoF) with a 49% reduction and wear resistance with a maximum 19% reduction. This study contributes valuable insights into optimizing bio-lubricant production derived from cottonseed oil through two-step transesterification, emphasizing its novel potential in improving frictional and wear characteristics.